The Effect of Mycorrhiza on Sorghum Plants in Dryland Areas - Ilwati, Uun; Sudharmawan, A. A. K; Sudantha, I Made (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Sorghum is one of the cereal crops that can grow well in dry land. However, dry land has limitations in terms of soil nutrients and its structure, which does not retain water for long. The productivity of sorghum in dry land is still low, at 2-3 tons/ha, which is far from its potential yield of 6-7 tons/ha. This happens because the soil lacks essential nutrients. Along with the application of both organic and synthetic fertilizers, one possible approach is to incorporate mycorrhiza into the soil. This article seeks to explore how mycorrhiza influences sorghum plants in arid conditions. This article serves as a review of existing literature concerning sorghum and the influence of mycorrhiza on its growth. From the findings and discussions presented, it can be inferred that mycorrhiza affects the uptake of nutrients, growth, and yield of sorghum by enhancing the availability and absorption of nutrients in the soil, boosting antioxidant activity, increasing photosynthesis, and improving the plants' resilience to environmental stress. Furthermore, mycorrhiza also affects the improvement of the plant's defense system by increasing dry matter content, keeping leaf stomata open, and helping the accumulation of substances including substances like soluble sugars, proline, glycine betaine, organic acids, potassium, and calcium within the plant, which helps in the uptake of water. The application of mycorrhiza to sorghum plants in dry land is expected to support the sustainable increase in plant productivity, reduce the use of chemical fertilizers, and promote a more environmentally friendly farming system.